Examining consumer behaviour toward genetically modified (GM) food in Britain - Spence, Alexa; Townsend, Ellen (Blackwell-Synergy, 2006)
This study examined behaviour towards genetically modified (GM) food in a British community-based sample. We used an equivalent gain task in which participants actually received the options they chose to encourage truthful responding. In conjunction with this, theory of planned behaviour (TPB) components were evaluated so as to examine the relative importance of behavioural influences in this domain. Here the TPB was extended to include additional components to measure self-identity, moral norms and emotional involvement. Results indicated that the monetary amounts participants accepted in preference to GM food were significantly lower than those accepted in preference to non-GM food. However, the vast majority of participants were indifferent between GM and non-GM food options. All TPB components significantly predicted behavioural intentions to try GM food, with attitudes towards GM being the strongest predictor. Self-identity and emotional involvement were also found to be significant predictors of behavioural intentions but moral norms were not. In addition, behavioural intentions significantly predicted behaviour, however, PBC did not. An additional measure of participants’ propensity to respond in a socially desirable manner indicated that our results were not influenced by self presentation issues giving confidence to our findings. Overall, it appears that the majority of participants (74.5%) would purchase GM food at some price.